Quantifying Acute Behavioral Reactions of Bali Mynas (Leucopsar rothschildi) to Environmental and Progressively Challenging Enrichment - Eli Baskir; Alayna Parsons; Marija Elden; David M. Powell (Journal of Zoological and Botanical Gardens, 2023)
Animals use specific behaviors and skills to overcome challenges and access resources. Environmental enrichment is provided to animals in human care to both promote species-appropriate behaviors and reduce undesired behaviors. Feather pecking in birds is an undesired behavior without a clear cause. The Saint Louis Zoo houses three pairs of young Bali mynas (Leucopsar rothschildi) who pluck neck feathers from conspecifics. To reduce this behavior, animal care staff presented the birds with seven enrichment items from four categories, presenting each item twice. The enrichment included a modifiable, progressively challenging bamboo tube device at multiple levels of difficulty. While plucking was not affected by any enrichment item, we observed significant increases in locomotion and decreases in autopreening, allogrooming, and head bobbing. Leafy greens produced the greatest changes when compared to other enrichment types. Overall engagement with the progressively challenging enrichment increased with the change from the first to the second level of difficulty, and interaction with the device was highest for the third and most difficult version. These increases suggest that no habituation to the progressively challenging device occurred, while a possible neophobic effect declined with multiple uses and increased familiarity.